2002
DOI: 10.1126/science.295.5560.1683
|View full text |Cite
|
Sign up to set email alerts
|

Flight of the Dodo

Abstract: The evolutionary history of the dodo is very poorly understood. Like many avian island endemics, a high degree of morphological change associated with flightlessness and gigantism has obscured phylogenetic relationships, and historically the dodo has been linked with avian tris (originally named for its dodolike beak) is the basal member of this strongly supported clade of large, generally ground-dwelling, island endemics. Furthermore, the phylogeographic distribution of this morphologically diverse clade sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 2 publications
12
98
2
4
Order By: Relevance
“…This tree is broadly in agreement with previous, less exhaustive phylogenetic analyses that included some members of this clade (Johnson et al 2001, Shapiro et al 2002, Pereira et al 2007); however, some important novel results emerged from our comprehensive analysis. Similarly to prior results, we estimated Claravis pretiosa as sister to the rest of the clade, with Uropelia estimated as sister to Metriopelia plus Columbina (Table 1).…”
Section: Discussion Phylogenetic Relationships Of Small New World Grosupporting
confidence: 80%
See 1 more Smart Citation
“…This tree is broadly in agreement with previous, less exhaustive phylogenetic analyses that included some members of this clade (Johnson et al 2001, Shapiro et al 2002, Pereira et al 2007); however, some important novel results emerged from our comprehensive analysis. Similarly to prior results, we estimated Claravis pretiosa as sister to the rest of the clade, with Uropelia estimated as sister to Metriopelia plus Columbina (Table 1).…”
Section: Discussion Phylogenetic Relationships Of Small New World Grosupporting
confidence: 80%
“…Several phylogenies have indicated that this group forms a monophyletic clade, although the placement of the clade within Columbidae is still unclear. Some phylogenies have placed the small New World ground doves as sister to the rest of the family (Johnson and Clayton 2000, Johnson 2004, Johnson et al 2010, but other work has placed the group as nested within the family (Shapiro et al 2002, Pereira et al 2007, Gibb and Penny 2010. Relationships among the species within this clade, however, have yet to be addressed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar results are found by two independent laboratories, one of which is a facility dedicated to aDNA research and has published numerous replicated aDNA studies (e.g. Cooper et al, 2001;Shapiro et al, 2002;Barnes et al, 2002;Endicott et al, 2003;Gilbert et al, 2003a, b). Secondly, the lack of contaminant DNA sequence variation observed between samples from one archaeological site and the much larger sequence variation between different sites points to the presence of contaminants in samples prior to extraction.…”
Section: Absence Of Authentic Y Pestis Dna In the Samplessupporting
confidence: 72%
“…R. Soc. B 283: 20152340 inferences of population divergence patterns solely on mtDNA [57][58][59][60] are probably reliable. However, our experimental design based on two-population comparison is relatively simple.…”
Section: Resultsmentioning
confidence: 99%